A treasury of Spurgeon on the life and work of our Lord ; v. 1 - Spurgeon, Charles Haddon, 1834-1892 (Grand Rapids, MI Baker, 1979)
Contents : v. 1 : Christ in the Old Testament
Keywords: Jesus Christ -- person and offices